BDNF Protein and BDNF mRNA Expression of the Medial Prefrontal Cortex, Amygdala, and Hippocampus during Situational Reminder in the PTSD Animal Model. (9th March 2021) - Chang, Shao-Han; Yu, Ying Hao; He, Alan; Ou, Chen Yin; Shyu, Bai Chuang; Huang, Andrew Chih Wei
Abstract : Whether BDNF protein and BDNF mRNA expression of the medial prefrontal cortex (mPFC; cingulated cortex area 1 (Cg1), prelimbic cortex (PrL), and infralimbic cortex (IL)), amygdala, and hippocampus (CA1, CA2, CA3, and dentate gyrus (DG)) was involved in fear of posttraumatic stress disorder (PTSD) during the situational reminder of traumatic memory remains uncertain. Footshock rats experienced an inescapable footshock (3 mA, 10 s), and later we have measured fear behavior for 2 min in the footshock environment on the situational reminder phase. In the final retrieval of situational reminder, BDNF protein and mRNA levels were measured. The results showed that higher BDNF expression occurred in the Cg1, PrL, and amygdala. Lower BDNF expression occurred in the IL, CA1, CA2, CA3, and DG. BDNF mRNA levels were higher in the mPFC and amygdala but lower in the hippocampus. The neural connection analysis showed that BDNF protein and BDNF mRNA exhibited weak connections among the mPFC, amygdala, and hippocampus during situational reminders. The present data did not support the previous viewpoint in neuroimaging research that the mPFC and hippocampus revealed hypoactivity and the amygdala exhibited hyperactivity for PTSD symptoms. These findings should be discussed with the previous evidence and provide clinical implications for PTSD.